Assessing the feasibility of heart rate variability as an objective indicator of anxiety in older adults with dementia living in care homes - Quinci, Milena A. (BMC Res Notes, 2021)
OBJECTIVE: Anxiety is reportedly prevalent in older adults with dementia living in care homes and, within this population, is most often assessed through caregiver reports. Heart rate variability (HRV) is a physiological indicator of autonomic function, whereby reduced vagally-mediated HRV is associated with a variety of anxiety symptoms and disorders. This study evaluates the feasibility of collecting HRV data within this population, presents HRV data for older adults with dementia living in a care home, and examines HRV in the context of self-reported anxiety. These data were collected during a larger study examining an exercise intervention. RESULTS: HRV data, in the form of log-transformed root mean square of the successive differences (lnRMSSD), were in line with transformed data from previous research. These data provide a promising direction for the use of wrist-worn devices in future HRV research with people living with dementia in care homes.